Individual’s awareness of healthy lifestyle: A cross sectional study of a rural community in Kedah, Malaysia - Fernandez, Kevin; Kharkwal, Kailash C.; Afrose, Tahmina; Habib, Nasrin; Das, Supraya (Journal of Biomedical Sciences, 2019)
Background: Healthy lifestyle practices play a key role in disease prevention and control of any chronic illness and disability. This study aims to identify the role of individual’s awareness towards a healthy life and well-being in a rural community Material and methods: This descriptive cross-sectional study was conducted by using structured questionnaire at a village, Kedah state, Malaysia on 2018. Results: The study revealed that among 120 respondents the mean ±SD age of respondents was 24±16.32 years. All the respondents were Muslim. The mean±SD weight of respondents was 66.07±14.353 kilogram. Study revealed that no participant reported drinking alcohol within the last month. 91 (76.6%) of the respondents were non-smoker. 42(35%) respondents reported daily consumption of fruits. 86 (71.67 %) respondents reported moderate to vigorous physical activities for 30 minutes per day. Regarding co-morbidity status, 60 (49.9%) was not suffering from any form of illness during the study period. This study found the significant association between the BMI and smoking habit with co-morbidity (p<0.000). Conclusion: Majority of the participants of this study was health conscious and had positive health-related behaviour. The effective behavioral changes less likely to happen unless the individual’s awareness and motivation towards a healthy life is decreased.